How far should a new leader reinterpret a school’s values to achieve improvement? - McGrath, Alexander (2011)
This dissertation considers the approach of a head teacher to the task of leading a new school, and provides a heuristic study of the question of whether, in order to be true to self, the head should reinterpret the stated values of the school to attune with his own. It examines the problem of reconciling the values of the leader and the school while leading a process of school improvement and serving the school and wider religious community which the school represents. The particular context is one of a faith school (in this case a Quaker school). The research is based on the writer’s own reflective process in reaching decisions on how best to proceed, and the personal challenge of reconciling his own values with those of the school, evidenced through a journal which reflected on significant events and private thought processes. Values are seen to be central to both authentic leadership and the process of galvanising a school community. The work identifies the importance of authenticity in leadership, and concludes by suggesting how the leader of a faith school might approach the challenge of leading a community by placing values at heart, and remaining true to self.